Stalking Behaviors Presented by Ex-Intimate Stalkers: A Victim’s Perspective - White, Eleanor (Journal of interpersonal violence, 2022)
Stalking can be defined as a pattern of repeated, unwanted behaviors by one person to another. These behaviors may take the form of communicative intrusion, third-party contact, and physical or sexual assault. The individual stalking behaviors experienced by victims have been found to differ in every case, specifically dependent on their stalker?victim relationship. Recent tragedies have shown that the police force generally underestimates the risk of ex-intimate stalking and harassment behaviors. This study aims to identify patterns of stalking behaviors from a victim?s perspective, specifically, whether there are any patterns of behavior among the ex-intimate stalkers, in comparison with acquaintance or stranger stalkers. Information from the accounts of individuals who had reported unwanted experiences as a result of one of three stalker?victim relationships (ex-intimate, acquaintance, or stranger) was extracted from the National Stalking Helpline database. Analyses were conducted on a sample of 1,626 victims? reports. One-way analysis of variance (ANOVA) and multiple logistic regressions were conducted to establish any common patterns of behavior among the subgroups of stalkers and to ascertain which behaviors increased the odds of being categorized as an ex-intimate stalker. Results indicated that ex-intimate stalkers presented considerably more behaviors than acquaintance or stranger stalkers; some of which included third-party contact, criminal damage, physical assault, and sexual assault. Results also indicated that ex-intimate stalkers presented more severe behaviors than the other subgroups. The majority of stalking behaviors were found to produce a statistically significant predictive contribution to being classed as an ex-intimate stalker. The findings in this study highlight that common misconception surrounding ex-intimate stalking still exists at every level of the Criminal Justice System. Results and implications for future research are discussed.